2016
DOI: 10.2174/0929867323666160525114735
|View full text |Cite
|
Sign up to set email alerts
|

From Bone Marrow to Cardiac Atrial Appendage Stem Cells for Cardiac Repair: A Review

Abstract: Traditionally the heart is considered a terminally differentiated organ. However, at the beginning of this century increased mitotic activity was reported in ischemic and idiopathic dilated cardiomyopathy hearts, compared to healthy controls, underscoring the potential of regeneration after injury. Due to the presence of adult stem cells in bone marrow and their purported ability to differentiate into other cell lineages, this cell population was soon estimated to be the most suited candidate for cardiac regen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…105,106 The only convincing strategy for clinically relevant cardiomyocyte differentiation requires substantial and direct epigenetic manipulation of BM-MSCs. [107][108][109] Therefore, it is assumed that in a normal physiological environment this type of stem cells can only rarely differentiate into functional cardiomyocytes.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…105,106 The only convincing strategy for clinically relevant cardiomyocyte differentiation requires substantial and direct epigenetic manipulation of BM-MSCs. [107][108][109] Therefore, it is assumed that in a normal physiological environment this type of stem cells can only rarely differentiate into functional cardiomyocytes.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%
“…Nevertheless, other important features of mature cardiomyocytes such as the generation of adult ventricular action potentials, specific ionic currents and the presence of gap junction proteins are not present in these cells 105,106 . The only convincing strategy for clinically relevant cardiomyocyte differentiation requires substantial and direct epigenetic manipulation of BM‐MSCs 107–109 . Therefore, it is assumed that in a normal physiological environment this type of stem cells can only rarely differentiate into functional cardiomyocytes.…”
Section: Stem Cell Types For Myocardial Repairmentioning
confidence: 99%
“…iPSCs originate from adult cells but are manipulated to gain similar differentiation abilities to ESCs. For decades researchers have been looking into specific stem cell populations [1] (e. g., iPSCs, [2][3][4][5][6][7] bone marrow-derived stem cells, [8][9][10][11][12] adipose tissue-derived stem cells, [13][14][15] dental pulp stem cells, [16][17][18] cardiac atrial appendage stem cells, [19][20][21][22] etc.) to regenerate tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The atrial appendage is traditionally used as a source of c-kit-positive cardiac stem cells [39, 40]. Additionally, in cultures derived from the atrial appendage, the presence of EC and SMC markers has been shown previously [41].…”
Section: Introductionmentioning
confidence: 99%